Recent Development in Magnetic Shape Memory Alloys - Chernenko, Volodymyr (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Heusler type magnetic shape memory alloys (MSMAs) have gained a strong academic and practical importance during recent decades due to the giant effects they exhibit, particularly magnetostrain produced by magnetic field-induced twin boundaries motion and magneto(elasto)-caloric effects resulting from the magnetic field-induced martensitic transformation. This Special Issue intends to communicate the latest advances in R&D and theory of MSMAs. This book consists of a collection of eleven invited peer-reviewed papers, each detailing a particular aspect in the fundamental and/or applied investigation of MSMAs and related phenomena. The papers are a corpus of up-to-date information on the ongoing studies of MSMAs. It is hoped that this reprint will be useful to physicists and materials scientists, both specialists and graduate students, and enable future technological breakthroughs in engineering.